DIFFERENCES OF MATERNAL SOCIODEMOGRAPHIC CHARACTERISTICS WITH SPONTANEOUS PRETERM BIRTH AMONG HOSPITALS IN INDONESIA: A COMPARATIVE STUDY - Herman, Sriyana; Santoso, Budi; Djoewono, Hermanto Tri (YCAB Publisher & IAKMI SULTRA, 2018)
Background: Maternal sociodemographic characteristics can be used to prevent preterm birth.Objective: To identify differences in maternal sociodemographic characteristics with spontaneous preterm birth among hospitals in East Java, Indonesia.Methods: This was a descriptive study with comparative design in 134 mothers who experienced preterm birth at eight hospitals. Data were analyzed using Independent samples t-test.Result: Sixteen variables were significantly different in maternal sociodemographic characteristics with spontaneous preterm birth among eight hospitals, namely: gestational age (CI 95%:10.97-0.02, p <0.049), maternal age (CI 95%:0.46-11.03, p <0.035), smoking (CI 95%:9.98-19.01 p <0.001), Edinburgh Postnatal Distress Scale (EPDS) (CI 95%:6.90-17.09, p <0.001), the fetus mobile (CI 95%:2.41-11.58, p <0.006), the number of visits during pregnancy (CI 95%:5.63-14.36, p <0.001), history of premature (CI 95%:7.76-15.73, p <0.001), history of disease (CI 95%:9.02-18.97, p <0.001), history of abortion (CI 95%:9.34-18.65, p <0.000), height (CI 95%:9.66-18.83, p <0.001), BMI (CI 95%:0.75-11.74, p <0.029), Mid Upper Arm Circumference (MUAC) (CI 95%:2.53-12.96, p <0.007), periodontal infection by (CI 95%:6.04-15.45, p <0.001), bleeding in young and old pregnancy (CI 95%:7.71-17.28, p <0.001), anemia status (CI 95%:2.30-10.19, p <0.004) and BV status (CI95%:9.05-20.45, p <0.001).Conclusion: There were significant disparities in maternal sociodemographic characteristics with preterm birth among hospitals. Our findings can be used as the basic data for future research in an effort to prevent premature birth disorders based on maternal sociodemographic characteristic.